776 A role for immune checkpoint blockade to enhance T cell-mediated responses in combination with chemotherapy in oesophageal adenocarcinoma. (10th December 2020) - Davern, Maria; Lysaght, Joanne; Sheppard, Andrew; Maher, Stephen; Donlon, Noel; Reynolds, John; Connell, Fiona; Hayes, Conall; King, Ross; Bhardwaj, Anshul
Abstract : Background: Combining immune checkpoint inhibitors (ICIs) with immunogenic chemotherapies is a promising approach in oesophageal adenocarcinoma (OAC) to convert 'cold' tumours to 'hot' tumours expanding the efficacy of ICIs to a greater spectrum of patients. 1 However, there is a vast array of immune checkpoints (ICs) expressed by T cells and the effect of ICIs in combination with chemotherapy regimens is largely unknown. 2 Methods: The expression profile of a range of ICs on circulating and tumour-infiltrating T cells was assessed using flow cytometry prior to and post-neoadjuvant treatment and correlated with clinical parameters (n=20). PBMCs isolated from OAC blood were treated with single agent ICIs alone (single agent anti-PD-1, anti-PD-L1, anti-A2aR and anti-TIM-3 inhibition) and in combination with FLOT (5-Fluorouracil, oxaliplatin and docetaxel) and CROSS (carboplatin and paclitaxel) chemotherapy regimens. The production of anti-tumour cytokines by T cells was assessed in vitro by flow cytometry (n=6). Results: In the treatment-naïve and post-treatment setting, a range of ICs were expressed by circulating T cells and were significantly increased on tumour-infiltrating T cells, which included PD-L1, PD-L2, CD160, PD-1, CTLA-4, TIGIT, TIM-3, LAG-3, A2aR and ICOS (p<0.05) (figure 1 ). Pre-treatment circulating PD-1+ T cells positively correlated with pathological nodal status (p<0.05), (figure 2 ). Whereas tumour-infiltrating CD3+CTLA-4+ cells positively correlated with nodal metastasis and lymphovascular invasion (p<0.05). The percentage of tumour-infiltrating CD3+CTLA-4+ and CD3+ICOS+ cells was significantly lower post-neoadjuvant treatment (p<0.05) (figure 3 ). However, post-neoadjuvant treatment circulating CD3+PD-1+ cells and CD3+CD4+TIGIT+ cells positively correlated with a better treatment response, determined by PET/CT (p<0.05), (figure 4 ). ICIs enhanced T cell production of anti-tumour cytokines IL-2 and IFN-y alone and in combination with chemotherapy in vitro from treatment-naïve OAC patients (p<0.05). Conclusions: T cells expressing ICs in circulation and infiltrating OAC tissue were adverse prognostic markers in the pre-treatment setting, perhaps due to their role in enabling tumour immune evasion and subsequent tumour progression. In contrast, T cells expressing ICs post-chemotherapy treatment in peripheral circulation were favorable prognostic markers. ICs are typically expressed by 'hot' tumours 2 therefore, the presence of ICs in the post-treatment setting may be as a result of an induced-anti-tumour immune response following immunogenic chemotherapy/chemoradiotherapy treatment and may be a useful strategy for stratifying patients into chemotherapy/chemoradiotherapy responders or non-responders. A therapeutic rationale is also highlighted for combining ICIs with chemotherapy regimens in OAC patients to enhance anti-tumour T cell-mediated responses and potentially boost response rates to chemotherapy treatment. Acknowledgements: We would like to thank all the patients who kindly donated their samples to our research Ethics Approval: The work was performed in accordance with the Code of Ethics of the World Medical Association (Declaration of Helsinki) for experiments involving human samples. Consent: Patients provided informed consent for sample and data acquisition, and the study received full ethical approval from the St. James's Hospital/AMNCH Ethical Review Board. References: Davern M, Lysaght J. Cooperation between chemotherapy and immunotherapy in gastroesophageal cancers. Cancer Lett 2020. https://doi.org/10.1016/j.canlet.2020.09.014 Emens LA, Middleton G. The interplay of immunotherapy and chemotherapy: harnessing potential synergies. Cancer Immunol Res 2015;3 :436–443.